Evaluacion preliminar de poblacion de cuatro especies de psitacidos de Tabasco, Mexico - Arriaga Weiá, S.L.
(Es, En)
Ilus., 9 ref.
Keywords: PSITTACIFORMES; PAJAROS; DISTRIBUCION GEOGRAFICA; EVALUACION; MEXICO